ANTIHYPERGLYCEMIC ACTIVITY, IMPROVING ENZIMATIC ANTIOXIDANT ACTIVITY OF ETHYL ACETATE FRACTION FROM KERSEN LEAVES (Muntingia calabura) ON INDUCED STREPTOZOTOSIN-NICOTINAMIDE RAT - Wicahyo, Septian Maulid; Pratama, Kharisma Jayak (Duta Pharma Journal, 2024)
Balance blood glucose concentration and antioxidant activity are keys to prevent Diabetes Melitus and its complications. Kersen leaves (Muntingia calabura) a plant that have empirical usage for reducing glucose blood that can do both. Purposes of this study were for observing ethyl acetate fraction from kersen leaves effects in reducing blood glucose, improving enzim antioxidant SOD and GPx activity, reducing MDA concentration and Î² cell regeneration. Forty two Wistar male white rats of 8 weeks with weight 150-250 g were made diabetes with streptozotosin-nicotinamide and randomly divided into 7 groups. Group I as normal rats, group II diabetic rats, group III diabetic with glibenclamid treatment, group IV and V diabetic rat treated by ethil acetate fraction 250 dan 350 mg/kg BW respectively. treatment had done orally once a day within 18 days. Blood glucose was measured on the 1st, 4th, 11th and 18th day. Ethyl acetate fractions significantly decreased blood glucose concentration, improved SOD and GPx activity, reduced MDA concentration and regenerated pancreatic Î²-cell also occured. In conclusion, ethyl acetate fraction have antihyperglycemic activity, ameliorates enzimatic antioxidant activity and can induce Î² cell regeneration.